ANALYSIS OF THE EFFECT OF MOLD TEMPERATURE AND MELT TEMPERATURE ON FILL TIME AND QUALITY PREDICTION OF PLASTIC PRODUCTS IN INJECTION MOLDING PROCESS USING AUTODESK MOLDFLOW ADVISOR SOFTWARE - Midarto Dwi Wibowo; Kusumawati Wahyuningsih (Politek ATK Yogyakarta Press, 2022)
This study aims to determine the effect of mold temperature and melt temperature on fill time and quality prediction of tablespoon products. This product is made of plastic with Polystyrene (PS) product material and is produced by the injection molding method. This research was conducted using Autodesk Moldflow Advisor software. From the results of this study, it is known that the best parameter setting among the twelve data obtained is at a mold temperature of 55°C and melt temperature of 220°C with a fill time of 0.2169 s and a high quality prediction of 13.80%, a medium value of 86, 20%, and a low value of 0.00%, because the quality of the resulting product is better and the production time is smaller. So that it can make the production process more effective and efficient